Three dimensional evaluation of the skeletal and temporomandibular joint changes following stabilization splint therapy in patients with temporomandibular joint disorders and mandibular deviation: a retrospective study - Madiha Mohammed Saleh Ahmed; Danli Shi; Majedh Abdo Ali Al-Somairi; Najah Alhashimi; Abeer A. Almashraqi; Mazen Musa; Ning Li; Xi Chen; Maged S. Alhammadi (BMC, 2023)
Abstract Background Three-dimensional (3D) detailed evaluations of the mandibular mediolateral position, mandibular condylar position, and temporomandibular joint (TMJ) spaces following stabilization splints (SS) therapy in patients with temporomandibular joint disorders (TMD) and mandibular deviation (MD) have not been reported in the available literature. Accordingly, this study aimed to three-dimensionally analyze the skeletal and bony temporomandibular joint changes following stabilization splint therapy in adult patients with temporomandibular joint disorders and mandibular deviation. Methods This study is a retrospective clinical study that enrolled 26 adult patients with TMD and MD with a mean age of 24.86 years. The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) was used to diagnose TMD. SS was adjusted weekly until occlusal contact stabilization occurred, and then adjusted monthly, patients were instructed to wear it at night for at least 10 h. The SS was removed after the elimination of TMD symptoms (TMJ/muscle pain on palpation, muscle spasm, and clicking) and having both condyles completely seated in a musculoskeletally stable position. Pre- and post-therapeutic Cone Beam Computed Tomography (CBCT) was analyzed. Mandibular mediolateral position, TMJ spaces, and mandibular condyle position were analyzed three-dimensionally using Mimics 21.0 software. Paired t-test or Wilcoxon rank-sum test was performed, and the significance level was considered at P < 0.05. Results The treatment period with SS therapy was 10.07 ± 3.1 months. The deviated chin was improved in 69.23% of the sample; the range of improvement was > 0 mm ≤ 3.9 mm. The mandibular rotation was significantly decreased from 3.58 ± 2.02° to 3.17 ± 1.60. The deviated side's superior and posterior joint TMJ spaces were significantly increased from 2.49 ± 0.88 mm and 1.25 ± 0.79 mm to 2.98 ± 1.02 mm and 1.86 ± 0.72 mm, respectively. The value of the difference from the bilateral condyle head position to the X and Z axes significantly decreased from 2.50 ± 1.56 mm and 2.30 ± 1.57 mm to 1.64 ± 1.58 mm and 1.82 ± 1.11 mm, respectively. Conclusion The main positional effect of the stabilization splint treatment in TMD patients with MD includes considerable correction of mandibular deviation, improving facial asymmetry, and moving the condyle into a stable condylar position; these were done by promoting the mandible to rotate around the Z (roll) and Y (yaw) axes and by forward, downward, and outward condylar movement on the deviated side, respectively.